Unexpected mitochondrial lineage diversity within the genus Alonella Sars, 1862 (Crustacea: Cladocera) across the Northern Hemisphere - Neretina, Anna N; Karabanov, Dmitry P; Sacherova, Veronika; Kotov, Alexey A (PeerJ, 2021)
Representatives of the genus Alonella Sars (Crustacea: Cladocera: Chydorinae) belong to the smallest known water fleas. Although species of Alonella are widely distributed and often abundant in acidic and mountain water bodies, their diversity is poorly studied. Morphological and genetic approaches have been complicated by the minute size of these microcrustaceans. As a result, taxonomists have avoided revising these species. Here, we present genetic data on Alonella species diversity across the Northern Hemisphere with particular attention to the A. excisa species complex. We analyzed 82 16S rRNA sequences (all newly obtained), and 78 COI sequences (39 were newly obtained). The results revealed at least twelve divergent phylogenetic lineages, possible cryptic species, of Alonella, with different distribution patterns. As expected, the potential species diversity of this genus is significantly higher than traditionally accepted. The A. excisa complex is represented by nine divergent clades in the Northern Hemisphere, some of them have relatively broad distribution ranges and others are more locally distributed. Our results provide a genetic background for subsequent morphological analyses, formal descriptions of Alonella species and detailed phylogeographical studies.
Keywords: Genetics; Cladocera; Phylogeography; Biogeography; Biodiversity